2021
DOI: 10.47836/pjtas.44.4.09
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Anti-termite Extracts from Four Saharan Plants against the Harvester Termite, Anacanthotermes ochraceus

Abstract: This study aimed to examine the anti-termite potential of four Saharan plant extracts, namely, the apple of Sodom or rubber bush, Calotropis procera; pergularia, Pergularia tomentosa; jimsonweed, Datura stramonium, and Egyptian henbane, Hyoscyamus muticus from Bechar (southwest of Algeria) on workers of the harvester termite, Anacanthotermes ochraceus (Isoptera: Hodotermitidae). A direct contact application test was conducted with five fractions from aqueous extracts of each part of plant species (leaves, stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Physical barriers are well-used to protect small buildings, although they are expensive [ 13 ]. Chemical termiticides such as aldrin, dieldrin, fipronil, and thiamethoxam were once widely used for subterranean termite control because of their efficacy and cost-effectiveness [ 8 , 10 , 14 ]. However, these chemicals cannot control damage to non-targeted organisms and cause ecological risks [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical barriers are well-used to protect small buildings, although they are expensive [ 13 ]. Chemical termiticides such as aldrin, dieldrin, fipronil, and thiamethoxam were once widely used for subterranean termite control because of their efficacy and cost-effectiveness [ 8 , 10 , 14 ]. However, these chemicals cannot control damage to non-targeted organisms and cause ecological risks [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that termites of this genus are the main pests of cocoa trees in Côte d'Ivoire [4,5]. Pesticidal plants represent, to date, the oldest form of pest control in agriculture [6]. With the advent of synthetic pesticides in 1940 and the spectacular results that were obtained with their use, the use of plants for pest control was relegated to the background and defined as a traditional method [7,8].…”
Section: Introductionmentioning
confidence: 99%